PENGARUH KEPUASAN KERJA, DAN KOMITMEN ORGANISASI TERHADAP TURNOVER INTENTION PADA THE DUSUN VILLA, SEMINYAK KUTA-BALI - Putru, Ida Bagus; Darmayanti, Ni Wayan Pramita (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2019)
The purpose of this study is: To determine the effect of job satisfaction on Turnover Intention in The Seminyak Village Seminyak Bali Kuta, To determine the effect of organizational commitment to Turnover Intention on The Seminyak Village Seminyak Bali Kuta. In thisstudy the census method is used by giving a questionnaire to the entire population of 42 people. The analysis used includes validity test,reliability test and classic assumption test, multiple linear regression, correlation, determination, F test and T test. Based on research and statistical analysis presented in the previous chapter, and in accordance with the research objectives, it can be concluded that employee job satisfaction has a negative and significant effect on employee turnover intentions at The Dusun Villa Seminyak Kuta Bali, while organizational commitment has a negative and significant effect on Turnover Intention employee at The Dusun Villa SeminyakKutaBali.